DEVELOPMENT OF A GOOGLE SITES-BASED 3-PHASE TRAINER KIT MODULE TO IMPROVE HOTS IN VOCATIONAL EDUCATION STUDENTS - Sapiro, Amanda Elena; Wiyono, Agus; Achmad, Fendi; Haryudo, Subuh Isnur; Rusimamto, Puput Wanarti (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to develop an alternative module-based model of Google Sites as a trainer kit, enhancing Higher Order Thinking Skills (HOTS) among participants in an electrical installation vocational high school. This research is unique in that it combines interactive web-based learning tools to develop critical thinking and problem-solving skills within technical education.Methodology – The Research type used in this study is R&D (Research and Development), employing methods of product testing on users both before and after implementation. The sample consists of 111 grade 11 students from three classes in a vocational high school, who are learning with a Google Sites-based module.Findings – Expert validation reveals that the media quality, content quality, and assessment parts of questionnaires achieve high scores; specifically, the assessment items score 93.37%, and the content score is 86.08%. Students' achievement, as measured by pre-test and post–test scores, presented a significant improvement, with an average N-Gain of 0.80, portraying a substantial increase in HOTS. Pre-test scores increased from 52.72 to 90.52 after the module was used.Contribution – This module development aligns with SDG 4 (Quality Education), which advocates for inclusive, equitable, and quality education, as well as the promotion of lifelong learning opportunities. The module was rated as practical, easy to use, and highly effective in enhancing student learning, with a usability score of 95.83%. Overall, the Google Sites-based trainer kit module has proven to be an effective tool for improving HOTS and advancing the quality of vocational education.